Hybrid Modal Realism Debugged. - Fouché, Camille (Erkenntnis, 2024)
In this paper, I support a hybrid view regarding the metaphysics of worlds. I endorse Lewisian Modal Realism for possible worlds (LMR). My aim is to come up with a hybrid account of impossible worlds that provides all the plenitude of impossibilities for all fine-grained intentional contents. I raise several challenges for such a plenitudinous hybrid theory. My version of hybrid modal realism builds impossible worlds as set-theoretic constructions out of genuine individuals and sets of them, that is, as set-theoretic constructions from parts and sets of parts of genuine Lewisian worlds. Structured worlds are defined as sets of tuples: structured entities built out of Lewisian 'raw material'. These structured worlds are ersatz worlds, some of which are impossible. I claim that propositions must be sets of worlds rather than members of sets. Once the construction is in place, I evaluate the proposal and show that my hybrid account is able to supply a plenitude of impossibilities and thus giving the resources to make all the hyperintensional distinctions we are looking for, whilst remaining Lewisian-conservative.